Biological Soil Crusts as Ecosystem Engineers in Antarctic Ecosystem - Barrera, Andrea; Acuña-Rodríguez, Ian S.; Ballesteros, Gabriel I.; Atala, Cristian; Molina-Montenegro, Marco A. (Frontiers in Microbiology, 2022)
Biological Soil Crusts (BSC) are considered as pivotal ecological elements among different ecosystems of the world. The effects of these BSC at the micro-site scale have been related to the development of diverse plant species that, otherwise, might be strongly limited by the harsh abiotic conditions found in environments with low water availability. Here we describe for the first time the bacterial composition of BSCs found in the proximities of Admiralty Bay (Maritime Antarctica) through 16s metabarcoding. Additionally, we evaluated their effect on soils (nutrient levels, enzymatic activity, and water retention), and on the fitness and performance of Colobanthus quitensis, one of the two native Antarctic vascular plants. This was achieved by comparing the photochemical performance, foliar nutrient, biomass, and reproductive investment between C. quitensis plants growing with or without the influence of BSC. Our results revealed a high diversity of prokaryotes present in these soil communities, although we found differences in terms of their abundances. We also found that the presence of BSCs is linked to a significant increase in soils’ water retention, nutrient levels and enzymatic activity when comparing with control soils (without BSCs). In the case of C. quitensis, we found that measured ecophysiological performance parameters were significantly higher on plants growing in association with BSCs. Taken together, our results suggest that BSCs in Antarctic soils are playing a key role in various biochemical processes involved in soil development, while also having a positive effect on the accompanying vascular flora. Therefore, BSCs would be effectively acting as ecosystem engineers for the terrestrial Antarctic ecosystem.